"Teaching is a lot more than just showing up to class and grading assignments": Preparing middle-level teachers for longevity in the profession. Issue 5 (20th October 2017) - Van Overschelde, James P.; Saunders, Jane M.; Ash, Gwynne Ellen
Abstract: The university's teacher preparation program has implemented and continually refined a professional development school program, with extended university-school relationships in its middle-level certification program. This program offers dialogue, targeted learning activities, and intensive field-based experiences to help ease preservice teachers from student identity to teacher identity. Preservice teachers spend several semesters working under the guidance of practicing middle-level teachers before assuming control of their own classrooms, mitigating potential reality shock and improving middle-level teacher retention. This program has led to higher than average 5-year retention rates for middle-level teachers. Recommendations for other teacher preparation programs are included.